In Their Own Words: How COVID-19 Has Impacted the Well-Being of Persons Living with Dementia in the Community. Issue 4 (December 2021) - McAiney, Carrie; Conway, Emma; Koch, Melissa; Middleton, Laura; Dupuis, Sherry; Keller, Heather; Dupuis, Kate; Lee, Linda; Fehr, Phyllis; Beleno, Ron; Kuepfer, Jane; Boger, Jennifer
Abstract: COVID-19 has had a devasting impact on older adults in Canada, including persons living with dementia. This intrinsic case study sought to understand the perceptions of persons living with dementia regarding how COVID-19 has impacted their well-being. Ten persons living with dementia participated in in-depth qualitative interviews about their experience with COVID-19. Using thematic analysis, four themes were identified: (1) expressing current and future concerns; (2) social connections and isolation; (3) adapting to change and resilience through engagement and hope; and (4) we're not all the same: reflecting individual experiences of the pandemic. Results highlight that while COVID-19 contributed to isolation, concerns, and frustrations, persons with dementia also demonstrated adaptation and resilience. This study reinforced that persons with dementia and their responses to challenges are unique. Therefore, interventions to support persons with dementia must also be individualized to each person's abilities and circumstances.